Safvet-beg Bašagić (1870-1934) Aux racines intellectuelles de la pensée nationale chez les musulmans de Bosnie-Herzégovine - Gelez, Philippe (Mondes méditerranéens et balkaniques (MMB), 2010)
Through his literary, historical and political oeuvre, Safvet-beg Bašagić (1870-1934) has formulated the great issues of bosnian-muslim nationalism, at a time when his community retreated from the demands placed upon it by the process of modernisation imposed by the austro-hungarian presence since the Berlin Congres of 1878. Inspired by ottoman, croat and serb nationalist movements of the 19th century, he attempted to establish an identity that was distinct from those of these movements by affirming the religious and cultural specificity of his fellow believers and compatriots. These engagements were intimately connected to the agrarian question in Bosnia-Herzegovina: Bašagić acted as a conservator, stressing that ownership of land was a historical right of the local beylicat, to which he belonged. During his lifetime he did not have the audience for which he would have wished; but the essential elements of his theses, despite their lack of scientific rigor, have flourished today.